Hypoxic re-exposure retains hematological but not performance adaptations post-altitude training - Yan, B.; Ge, X.; Yu, J.; Hu, Y.; Girard, O. (European Journal of Applied Physiology, 2021)
Purpose: To test the hypothesis that hypoxic re-exposure after return from natural altitude training is beneficial in retaining hematological and performance adaptations. Methods: Eighteen mixed martial art fighters completed a 3-weeks natural altitude training camp at 2418 m. Afterwards, participants were randomly assigned to a living high-training low (12 h/d at a simulated altitude of 2800 m) group (LHTL, n = 9) or a living low-training low group (LLTL, n = 9) for a 3-week sea-level training period. At baseline and after return to sea level, hematological [hemoglobin mass (Hbmass) on days 2, 6, 9, 12, 15 and 21] and performance (3000 m time trial and maximal oxygen uptake on days 4, 6, 9, 15 and 21) markers were assessed. Results: Mean Hbmass increased from baseline to day 2 (11.7 ± 0.9 vs. 12.4 ± 1.3 g/kg; + 6.6 ± 7.5%; P < 0.05). While Hbmass remained elevated above baseline in LHTL (P < 0.001), it returned near baseline levels from day 9 in LLTL. Irrespective of groups, mean V?O2max was only elevated above baseline at day 2 (+ 4.5 ± 0.8%) and day 9 (+ 3.8 ± 8.0%) (both P < 0.05). Compared to baseline, 3000 m running time decreased at day 4 (- 3.1 ± 3.3%; P < 0.05) and day 15 (- 2.8 ± 2.3%; P < 0.05) only. Conclusions: Despite re-exposure to hypoxia allowing a recovery of the hypoxic stimulus to retain Hbmass gains from previous altitude sojourn, there is no performance advantage of this practice above sea level residence. Our results also give support to empirical observations describing alternance of periods of optimal and attenuated performance upon return to sea level.